Growth Factor Deregulation and Emerging Role of Phosphatases in Diabetic Peripheral Artery Disease - Mercier, Clément; Rousseau, Marina; Geraldes, Pedro (Frontiers in Cardiovascular Medicine, 2021)
Peripheral artery disease is caused by atherosclerosis of lower extremity arteries leading to the loss of blood perfusion and subsequent critical ischemia. The presence of diabetes mellitus is an important risk factor that greatly increases the incidence, the progression and the severity of the disease. In addition to accelerated disease progression, diabetic patients are also more susceptible to develop serious impairment of their walking abilities through an increased risk of lower limb amputation. Hyperglycemia is known to alter the physiological development of collateral arteries in response to ischemia. Deregulation in the production of several critical pro-angiogenic factors has been reported in diabetes along with vascular cell unresponsiveness in initiating angiogenic processes. Among the multiple molecular mechanisms involved in the angiogenic response, protein tyrosine phosphatases are potent regulators by dephosphorylating pro-angiogenic tyrosine kinase receptors. However, evidence has indicated that diabetes-induced deregulation of phosphatases contributes to the progression of several micro and macrovascular complications. This review provides an overview of growth factor alterations in the context of diabetes and peripheral artery disease, as well as a description of the role of phosphatases in the regulation of angiogenic pathways followed by an analysis of the effects of hyperglycemia on the modulation of protein tyrosine phosphatase expression and activity. Knowledge of the role of phosphatases in diabetic peripheral artery disease will help the development of future therapeutics to locally regulate phosphatases and improve angiogenesis.